Entrepreneurship and Digital Product Monetization in Fintech: A Framework for Emerging Market Scalability - Solomon Christopher Friday; Oluwasanmi Segun Adanigbo; Florence Sophia Ezeh; Comfort Iyabode Lawal; Unomah Success Ugbaja (International Journal of Scientific Research in Computer Science, Engineering and Information Technology, 2025)
This paper explores the dynamic intersection of entrepreneurship and digital product monetization within the context of FinTech, with a focus on scalability in emerging markets. As the global financial landscape continues to evolve, FinTech has emerged as a transformative force, offering innovative solutions to address gaps in financial inclusion and accessibility. The paper discusses how entrepreneurs can leverage digital product monetization strategies such as subscription models, transaction fees, and freemium offerings to generate sustainable revenue while expanding their market presence. Challenges such as technological limitations, economic instability, regulatory complexities, and social barriers to adoption are examined in-depth, along with strategies for overcoming these hurdles. The paper further explores the role of innovation in driving growth and scalability, highlighting the importance of technological advancements such as artificial intelligence, blockchain, and machine learning. It concludes with actionable policy and entrepreneurial recommendations aimed at fostering an environment conducive to FinTech growth in emerging economies, ensuring sustainable and inclusive financial solutions for the future.